Structure and Phase Composition of Tempered Martensite Steel After Severe Plastic Deformation - Nikonenko A. Alisa; Popova N. Natalya; Nikonenko E. L. Elena Leonidovna; Sizonenko N. Nina; Koneva N. Nina (Modification of materials structure and properties, 2017)
Title screen